2014
DOI: 10.3349/ymj.2014.55.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Reperfusion Therapy and Hospital Mortality in ST-Elevation Myocardial Infarction Patients with Non-Chest Pain Complaints

Abstract: PurposeST-elevation myocardial infarction (STEMI) patients may visit the emergency department (ED) complaining of sensations of pain other than the chest. We investigated our performance of reperfusion therapy for STEMI patients presenting with non-chest pains.Materials and MethodsThis was a retrospective observational cohort study. STEMI patients who underwent primary percutaneous coronary intervention (PCI) were divided into a chest pain group and a non-chest pain group. Clinical differences between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…[ 11 , 24 , 32 , 33 , 37 , 46 , 47 ] Fatigue, weakness or lethargy also accounted for high proportions of presentations, spanning 4.3%– 60% across 15/41 studies; when investigated, atypical chest pain (n=12/41), also described as non-specific, pleuritic or burning, was another common symptom, reported in 11.1%–72%. [ 29 , 32 , 42 , 48 ] Nausea and vomiting were also identified with high frequency (n=21/41) and proportion (range 1.7%–25.8%) although, again, were reported as distinct symptoms, combined or consolidated as gastrointestinal symptoms. [ 9 , 11 , s24 , 28 , 33 , 35 , 37 , 40 – 45 , 49 55 ] Notably, diaphoresis (including sweating, clammy skin and perspiration) featured in 12/41 studies in a reported range of 2.4%–27.9%.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 , 24 , 32 , 33 , 37 , 46 , 47 ] Fatigue, weakness or lethargy also accounted for high proportions of presentations, spanning 4.3%– 60% across 15/41 studies; when investigated, atypical chest pain (n=12/41), also described as non-specific, pleuritic or burning, was another common symptom, reported in 11.1%–72%. [ 29 , 32 , 42 , 48 ] Nausea and vomiting were also identified with high frequency (n=21/41) and proportion (range 1.7%–25.8%) although, again, were reported as distinct symptoms, combined or consolidated as gastrointestinal symptoms. [ 9 , 11 , s24 , 28 , 33 , 35 , 37 , 40 – 45 , 49 55 ] Notably, diaphoresis (including sweating, clammy skin and perspiration) featured in 12/41 studies in a reported range of 2.4%–27.9%.…”
Section: Resultsmentioning
confidence: 99%
“…However, clinical studies have shown that the possibility of incomplete myocardial reperfusion after coronary recanalization can reach as high as 37 to 43%. If not found in time, disease progression would lead to complete myocardial necrosis, expanded infarct size and ventricular remodeling, leading to heart failure, increased risk of arrhythmia, and a 5–10 times increase in patient mortality ( 7 , 8 ). In order to improve the prognosis of patients, researchers have continuously worked to establish a score system that can objectively reflect the risk factors of malignant heart events after reperfusion treatment, which could assist physicians in determining a timely and accurate case-based reasonable and effective treatment program, and reduce the occurrence of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have, moreover, reported that there was no significant difference in mortality in patients with AMI admitted during regular versus off-hours. 19 21 22 However, in one study, patients with AMI admitted during off-hours were less likely to undergo primary PCI and more likely to undergo fibrinolytic therapy. Consequently, there was no difference in the overall usage of reperfusion therapy, irrespective of the arrival time.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, presentation without chest pain was an independent predictor of hospital mortality in patients with STEMI after primary PCI. 19 Unfortunately, the acquisition of an ECG may be omitted in the initial assessments of these patients to the ED, and a delayed door-to-data interval may be the most critical factor for longer door-to-balloon times in patients with STEMI. Thus, standardisation of the door-to-data protocol can help improve early recognition in emergency situations.…”
Section: Discussionmentioning
confidence: 99%